ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN DALAM PENYAJIAN LAPORAN KEUANGAN - Ellyn Agna Safitri; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to explain the application of environmental accounting in the presentation of financial statements at the Islamic Hospital of the Islamic University of Malang. This research is a descriptive qualitative research. Data collection techniques that can be in the form of interviews) and methods of observation and data analysis are descriptive model methods. The results of the study stated that the information obtained from interviews with 7 (seven) informants was known that the Islamic Hospital of the Islamic University of Malang had not yet implemented environmental accounting. However, costs related to environmental accounting or the application of waste management have been included in the financial statements and in the presentation of the financial statements, they are free from material errors, and present factual and verifiable data, because the financial statements of the Malang Islamic University Hospital have been published. corrected by several parties, ranging from the team in charge of waste management to the hospital manager.Keywords: Environmental Accounting and Financial Reports